Is this right? I'm not sure if I'm on the right track.(adsbygoogle = window.adsbygoogle || []).push({});

Using the definition of derivate find f ` (x)

f (x) = x - (a/x) , where a is a constant

f ` (x) = lim h->0 [(f(x+h)) – (f(x))]/h

= lim h->0 [((x+h) –(a/(x+h)) -(x-(a/x))]/h

= lim h->0 ([((x+h) –(a/(x+h)) -(x-(a/x))]/h) . (x(x+h))/(x(x+h))

= lim h->0 ((x^3)+(h^2x)-(ax)-(x^3)-(x^2h)+(ax)+(ah))/(h(x^2+xh))

= lim h->0 (h(hx-x^2+a))/(h(x^2+xh)) = (-x^2+a)/x^2

**Physics Forums | Science Articles, Homework Help, Discussion**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Help with a derivative

**Physics Forums | Science Articles, Homework Help, Discussion**